THE USE OF PHYSICAL CULTURE METHODS IN PRESCHOOL CHILDREN WITH TUBERCULOUS INTOXICATION IN THE PROCESS OF THE BASIS FORMATION OF HEALTHY LIFESTYLE IN THE CHILDREN’S PRE-SCHOOL ESTABLISHMENT - O. V. Galaziy (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The use of the physical culture methods in the children's pre-school establishment promote health status improving in children with tuberculosis intoxication, normalizes the psycho-emotional condition of the children, promote of the basis formation of the healthy lifestyle.